La corrupción y el futuro de America Latina (Società e diritti, 2020)
The corruption in Latin America is analyzed, its social and political aspect. The social model and its manifestation are discovered. Corruption is examined above all with information from recent criminal investigations in Brazil and Peru, in which large Brazilian and peruvian multinationals are involved, whose acts of corruption are of great magnitude due to the great bribes they would have made to governments of at least, ten countries in Latin America.